Nuclear-resident RIG-I senses viral replication inducing antiviral immunity - GuanQun Liu (Nature Portfolio, 2018)
RIG-I senses cytoplasmic viral RNA, resulting in induction of an antiviral response. Here, the authors identify nuclear RIG-I and show that it binds nuclear influenza A virus RNA, resulting in a cooperative interferon induction along with its cytoplasmic counterpart.